Qur’anic and Hadith-Based Ecological Education as a Non-Formal Approach to Address Environmental Pollution - Rifai, Ahmad; Zahro Nafiza, Azka; Nul Hakim, Lukman; Hidayat, Rahmat (Cendekia: Kependidikan dan Kemasyarakatan, 2025)
Environmental pollution has become a serious issue in metropolitan areas, including Palembang, with a direct impact on community health and quality of life, particularly in relation to waste management at the final disposal site (Tempat Pembuangan Akhir/TPA). This study aims to explore ecological messages in the Qur’an and Hadith and examine their potential contribution to strengthening faith-based ecological awareness through non-formal Islamic education. This study employed a qualitative approach using a library research design. This study used the Tafsir Mawdu’iy. The data were collected from Qur’anic verses, Hadith, classical and contemporary tafsir, and scholarly literature on ecology and environmental education. Then, they were analysed contextually by integrating scientific and social perspectives. References to community-based educational practices around the Sukawinatan landfill are drawn from secondary sources and documented studies rather than direct field observation. The findings reveal that Qur’anic and Hadith-based ecological education can enhance faith-based environmental awareness. It is reflected in community initiatives such as tree planting and pollution reduction efforts. This study concludes that integrating Islamic ecological teachings into non-formal education has the potential to promote clean and healthy living behaviors and support sustainable environmental management.